Comparison of anticandidal activity of Punica granatum (Pomegranate) and Lawsonia inermis (Henna leaves): An in-vitro study - Singla, Swati; Gupta, Rakhi; Puri, Abhiney; Bhardawaj, Virendar Singh; Roy, Swati (International Journal of Dental Research, 2013)
Background: Oral Candidosis is common opportunistic infection of the oral cavity caused by overgrowth of Candida species, the commonest being Candida albicans. Increasing resistance and side effects of the antifungal drugs used in therapy of candidosis have given way to the use of natural products. Pomegranate and Henna have been found to be very effective in the treatment of Candidosis. Aim of study: This study evaluates the antifungal activities of pomegranate peel extract (rind), pomegranate seed extract (Punica granatum) and Henna leaves (Lawsonia inermis) against different strains of Candida albicans. Materials and methods: Both aqueous and ethanolic extracts of pomegranate peel, seeds and henna leaves were prepared. Anticandidal activity was determined and minimum zones of inhibitions (in mm) shown by extracts of all the three plants were measured and compared. Results: Henna leaves showed the maximum zone of inhibition (mean 20 mm) followed by pomegranate peels (mean 13.3 mm) and seeds (mean 3.75mm). Also, aqueous extracts of henna and pomegranate showed higher antifungal activity as compared to their corresponding ethanolic extracts. Conclusion: Use of medicinal plants against candida can be a viable alternative to other antifungal agents as they offer a cheap and effective module used in control of oral infections caused by Candida species.